2018
DOI: 10.1371/journal.pone.0207426
|View full text |Cite
|
Sign up to set email alerts
|

The differential effects of type and frequency of social participation on IADL declines of older people

Abstract: BackgroundAlthough social participation (SP) is valid in active aging, it is vague which types and the frequency of SP are effective in maintaining instrumental activities of daily living (IADL). We conducted a community-based prospective cohort study and investigated the association of the types and frequency for SP with IADL decline in community-dwelling older adults.MethodsThe target population were all individuals aged ≥65 living in a commuter town in Nara, Japan. A total of 6,013 participants with indepen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
37
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(43 citation statements)
references
References 48 publications
(104 reference statements)
3
37
3
Order By: Relevance
“…The analysis of the number of organizations revealed the HRs of the number of types of organizations progressively decreased as the number of participating organizations. This supports previous studies, including those measuring other health outcomes [10,13,[16][17][18]. In this study, HRs were lower when participated in two or more types of organizations in rural areas than in urban areas.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…The analysis of the number of organizations revealed the HRs of the number of types of organizations progressively decreased as the number of participating organizations. This supports previous studies, including those measuring other health outcomes [10,13,[16][17][18]. In this study, HRs were lower when participated in two or more types of organizations in rural areas than in urban areas.…”
Section: Discussionsupporting
confidence: 90%
“…According to this result, a good public health policy would include local government provision of regular opportunities for social participation in sports and hobbies in both rural and urban areas. Participation in sports and hobby groups has also been reported to prevent other poor health outcomes [16,18,19]. Previous studies have shown that older people in rural areas were unhealthier than older people in urban areas [20,24,29,30], but in this study, there was no difference in the incidence of functional disability between older people in rural and urban areas.…”
Section: Discussioncontrasting
confidence: 65%
See 3 more Smart Citations